2021
DOI: 10.3803/enm.2021.1274
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two DXA Systems, Hologic Horizon W and GE Lunar Prodigy, for Assessing Body Composition in Healthy Korean Adults

Abstract: Background: Dual-energy X-ray absorptiometry (DXA) is the most widely used method for evaluating muscle masses. The aim of this study was to investigate the agreement between muscle mass values assessed by two different DXA systems.Methods: Forty healthy participants (20 men, 20 women; age range, 23 to 71 years) were enrolled. Total and regional body compositional values for fat and lean masses were measured consecutively with two DXA machines, Hologic Horizon and GE Lunar Prodigy. Appendicular lean mass (ALM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…To explore the magnitude of potential DXA scanner differences, we compared Hologic Discovery and GE Lunar iDXA estimates of ALM in our laboratory (Supplementary Fig. 3 ), similar to the study reported by Park et al 14 that compared Hologic Horizon and GE Lunar Prodigy scanners. Although ALM measured by both DXA systems in our laboratory were highly correlated (n = 45; R 2 , 0.99), average scanner differences (X ± SD; 0.54 ± 0.58 kg; p < 0.001) and significant bias (p < 0.05) were present.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…To explore the magnitude of potential DXA scanner differences, we compared Hologic Discovery and GE Lunar iDXA estimates of ALM in our laboratory (Supplementary Fig. 3 ), similar to the study reported by Park et al 14 that compared Hologic Horizon and GE Lunar Prodigy scanners. Although ALM measured by both DXA systems in our laboratory were highly correlated (n = 45; R 2 , 0.99), average scanner differences (X ± SD; 0.54 ± 0.58 kg; p < 0.001) and significant bias (p < 0.05) were present.…”
Section: Discussionmentioning
confidence: 91%
“…Although ALM measured by both DXA systems in our laboratory were highly correlated (n = 45; R 2 , 0.99), average scanner differences (X ± SD; 0.54 ± 0.58 kg; p < 0.001) and significant bias (p < 0.05) were present. Park et al 14 found between-scanner ALM differences of 1.79 ± 0.92 kg (p < 0.001). These kinds of between DXA and MRI system measurement differences are likely part of the reason why we found small mean differences and bias between our SM predictions and those of Kim et al 8 …”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Importantly, participants were representative of the populations usually imaged at these two research facilities meaning that the corrections should be applicable in our context. While studies have been published detailing the cross-calibration of different modalities in hospital or research settings, to date these have been from high income settings [4,8,13,14,[19][20][21][22][23][24][25][26]. To the best of our knowledge, this represents the first such study in sub-Saharan Africa, where research sites with dedicated bone imaging facilities are few, and hospitals have limited access to standard clinical modalities such as DXA.…”
Section: Discussionmentioning
confidence: 99%
“…For one of the studies, 41 DXA scanning instrumentation was manufactured by Hologic, Inc. For the other 2 studies, 42,43 Lunar scanning instrumentation from GE HealthCare was used. Because the 2 instrument sources do not yield identical results, [44][45][46] quantitative readings obtained from the Lunar instrument were converted to the equivalent Hologic readings based on studies in which DXA scanning was performed on the same individuals using both Lunar and Hologic instrumentation. 44 Using the regression coefficients generated from the above analysis of the NHANES 2003-2006 group, the independent anthropometric variables in the ELS subjects were used to calculate PTBF for the individual ELS participants.…”
Section: Methodsmentioning
confidence: 99%